P3-S1.16 Comparison of the Abbott m2000 RealTime CT assay for Chlamydia trachomatis monitoring in Tanzania compared to the Roche Amplicor CT assay. (10th July 2011) - Agreda, P; Dize, L; West, S; Williams, J A; Van Der Pol, B; Gaydos, C A
Abstract : Background: The Abbott m2000 RealTime CT assay was evaluated as a new option for the detection of Chlamydia trachomatis in specimens obtained from Tanzania, and its performance was compared to the performance of the Roche Amplicor CT Assay. Methods: Duplicate swab specimens were collected from villages throughout Tanzania. 304 duplicate samples were shipped to the Johns Hopkins STD laboratory at 2–8°C for the detection of C trachomatis . All swab specimens were shipped in a dry state, expressed in 1 ml of sterile molecular grade DEPC water upon arrival, and analysed using the Roche Amplicor CT assay. Prior to Roche Amplicor amplification and detection, DNA extraction was performed using the Roche Magna Pure LC robot. The duplicate swab specimens were shipped to Indiana University for Abbott m2000 RealTime CT assay analysis. The bacterial load was measured by the DC value of the m2000 RealTime CT. Results: Of 304 specimens, 44 (14.5%) were positive for CT via Roche Amplicor CT assay, and 53 (17.4%) were positive for CT via Abbott m2000 RealTime CT assay. The relative quantitation for the m2000 assay ranged from DC 0.62 to DC 22.16. If the Roche PCR assay was considered to be the reference standard, the Abbott m2000 RealTime CT assay sensitivity was 44/44 (100%), specificity was 251/260 (96.53%), positive predictive value was 251/251(100%), and negative predictive value was 44/53 (83.01%). The κ score was 0.890. Discordant specimens, which were determined to be negative by Roche Amplicor and positive by Abbott m2000 RealTime, were tested by Gen-Probe TMA. Of nine discordant tests, two were positive, five were negative, and two were of insufficient volume for retesting. After discordant testing, there appeared to be five samples that were graded to be false positives by m2000. The Abbott m2000 RealTime CT assay sensitivity remained 100%, while specificity increased to 256/258 (99.2%). The negative predictive value increased to 46/48 (95.83%). The κ score was 0.9748 after discordant results were further analysed. Conclusions: Abbott m2000 RealTime CT assay demonstrates excellent sensitivity and specificity compared to the Roche Amplicor CT Assay for the detection of C trachomatis . It may be advantageous to be able to measure the relative concentration for CT in some epidemiologic studies.